Endocytosis in filamentous fungi - Kalkman, Edward R I C (My University, 2007)
Endocytosis is little understood in filamentous fungi. For some time it has been controversial as to whether endocytosis occurs in filamentous fungi. A comparative genomics analysis between Saccharomyces cerevisiae and 10 genomes of filamentous fungal species showed that filamentous fungi possess complex endocytic machineries. The use of the endocytic marker dye FM4-64, and various vesicle trafficking inhibitors revealed many similarities between endocytosis in the filamentous fungus Neurospora crassa, and endocytosis in budding yeast and mammalian cells. Actin polymerization was found to be crucial for endocytosis in N. crassa, and the microtubule cytoskeleton seemed to be necessary for long distance movement of putative early endosomes. Brefeldin A (BFA) blocked vesicular transport to the Spitzenkörper. Three putative endocytic proteins (WASP, clathrin light chain and Rab5) were labelled with fluorescent proteins in N. crassa. WASP-GFP was found to localise to motile, punctate structures in the plasma membrane just behind the hyphal apex in growing hyphae. This localisation changed to the hyphal apex when growth was temporarily arrested, indicating a possible role in endocytosis and polarized growth. Clathrin light chain-GFP was found to be concentrated in a region just behind the Spitzenkörper, which is consistent with there being a high concentration of clathrinmediated endocytosis in this region. Clathrin light chain-GFP also labelled putative Golgi and this labelling was found to be BFA sensitive, whereas BFA did not have a detectable effect on FM4-64 internalisation and organelle staining. GFP-Rab5 labelled putative early endosomes and decorated microtubules. Knock-outs of putative endocytic proteins in N. crassa, generated as part of the Neurospora genome consortium gene knock-out project, were analysed for defects in endocytosis. 14 out of 17 gene knock-outs were found to be ascospore lethal. The Rab5 knock-out was viable, but did not show a detectable effect on the endocytic internalisation of FM4-64 or its pattern of staining. However, it did exhibit a defect in sexual crossing.
Keywords: biological sciences; cell biology